Faraway, so close: Coupled climate and economic dynamics in an agent-based integrated assessment model - Francesco Lamperti; Giovanni Dosi; Mauro Napoletano; Andrea Roventini; Alessandro Sapio (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2017)
In this paper we develop the first agent-based integrated assessment model, which offers an alternative to standard, computable general-equilibrium frameworks. The Dystopian Schumpeter meeting Keynes (DSK) model is composed of heterogeneous firms belonging to capital-good, consumption-good and energy sectors. Production and energy generation leads to greenhouse gas emissions, which affect temperature dynamics in a non-linear way. Increasing temperature triggers climate damages hitting, at the micro-level, workers' labor productivity, energy efficiency, capital stock and inventories of firms. In that, aggregate damages are emerging properties of the out-of-equilibrium interactions among heterogeneous and boundedly rational agents. We find the DSK model is able to account for a wide ensemble of micro and macro empirical regularities concerning both economic and climate dynamics. Moreover, different types of shocks have heterogeneous impact on output growth, unemployment rate, and the likelihood of economic crises. Finally, we show that the magnitude and the uncertainty associated to climate change impacts increase over time, and that climate damages are much larger than those estimated through standard integrated assessment models. Our results point to the presence of tipping points and irreversible trajectories, thereby suggesting the need of urgent policy interventions.
Keywords: C63; Q40; Q50; Q54; 330; Climate Change; Agent-Based Models; Integrated Assessment; Macroeconomic Dynamics; Climate Damages